Implementation of Da’wah Program in Brunei Darussalam: An Overview from Brunei Radio Television and Islamic Da’wah Center - Muhammad Akmal Bin Awang Tarif; Cecep Soleh Kurniawan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Da'wah is obligatory for every Muslim. Therefore, in Muslim societies, da'wah is conducted by various parties, including the government. In this paper, the researchers focus more on the da'wah program carried out by two government institutions in Brunei Darussalam, namely Radio Television Brunei and the Islamic Da'wah Center. These two institutions work hand in hand to help the success of da'wah programs in Brunei Darussalam. This article uses qualitative methods. It collects data from written resources such as books, newspapers, documents and others. Data is analyzed based on historical approach. This article finds that due to the da'wah programs of the Islamic Da'wah Center until 2020, the number of converts is increasing, and the Dusun Tribe is the largest ethnic group that converted to Islam in the last five years. This conversion is a good achievement in da'wah, especially in rural areas. This achievement is in line with Brunei Darussalam government programs to support the development of da'wah continues to live and thrive in the broader community in Brunei Darussalam.